1983
DOI: 10.1021/ja00352a014
|View full text |Cite
|
Sign up to set email alerts
|

Detailed absorption, reflectance, and UV photoelectron spectroscopic and theoretical studies of the charge-transfer transitions of tetrachlorocuprate(2-) ion: correlation of the square-planar and the tetrahedral limits

Abstract: Low-temperature (7 K) polarized single-crystal absorption and room-temperature polarized specular reflectance spectra have been obtained of the chloride-to-copper charge-transfer region of the three known square-planar salts of CuCl42", bis(methadonium) tetrachlorocuprate(II), bis(TV-methylphenethylammonium) tetrachlorocuprate(II), and bis(creatinium) tetrachlorocuprate(II) and of the tetragonal monomer, bis(ethylammonium) tetrachlorocuprate(II). These spectra show two intense, x-y polarized, x-y split transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 1 publication
11
88
0
Order By: Relevance
“…2, Inset), confirming the presence of chloride in the equatorial plane (45,(49)(50)(51)(52)(53) (Fig. 3A).…”
Section: Resultssupporting
confidence: 63%
“…2, Inset), confirming the presence of chloride in the equatorial plane (45,(49)(50)(51)(52)(53) (Fig. 3A).…”
Section: Resultssupporting
confidence: 63%
“…In this framework by fitting the experimental data we estimated the gap energy of the (C 2 H 5 NH 3 ) 2 CuCl 4 film, E g , to be 3.32±0.02 eV Optical absorption measurements The optical absorption was measured at room temperature for quartz substrate deposited films, in the 9000-52000 cm -1 range. The absorbance spectra were consistent with previous results [1,7,14,18,19], thus confirming that the films have sufficient structural and optical quality. The absorption spectra are shown in fig.…”
Section: Resultssupporting
confidence: 90%
“…The two UV bands were assigned to charge transfer (CT) transitions occurring in the axially elongated CuCl 6 4-octahedron. In particular, the 35500 cm -1 band was claimed to correspond to the σ→d x 2 -y 2 transition and the 26000 cm -1 one to the π→d x 2 -y 2 (e u →b 1g ) transition [18,19]. In the case of (C 2 H 5 NH 3 ) 2 CuCl 4 film we found that the first UV band is centred at 26200 cm -1 .…”
Section: Resultsmentioning
confidence: 70%
“…For the ligand Br, the above contributions rapidly increase to almost 4 and 8 times those of the respective CF terms. This can be ascribed to the much larger ζ p 0 (≈ 2460 cm −1 [34]) and lower CT energy levels for [CuBr 4 ] 2− cluster than that for [CuCl 4 ] 2− cluster [18,36]. The importance of the CT contributions for the hyperfine structure constants is less significant than that for the g factors due to the large isotropic part characterized by the core polarization constant.…”
Section: Discussionmentioning
confidence: 99%
“…The core polarization constants in the formulas of the hyperfine structure constants are taken as κ ≈ 0.3 [32,35], the expectation value for Cu 2+ in tutton salts. The CT energy levels E CT1 and E CT2 are about 38000 cm −1 and 35000 cm −1 [36] for K 2 PdCl 4 , and 30500 cm −1 and 27500 cm −1 [18] for K 2 PdBr 4 , respectively. Substituting these values into (8), the theoretical EPR parameters (Cal.…”
Section: Brmentioning
confidence: 94%